TANGGAPAN MAHASISWA TINGKAT I (2015/2016) TERHADAP PENERAPAN MEDIA POWER POINT DALAM MEMAHAMI PENGGUNAAN KATA BANTU BILANGAN Tsu, Hon, Ko, Hai PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Rahmayati '; Merri Silvia Basri; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study sought to determine the results of questionnaires and interviews students about the application of media power point on the course Bunpou 1 auxiliary word material numbers～tsu、～hon、～ko、～hai. This study aims to determine students' responses on the application of media power point, namely, the positive things that earned the student, and the constraints faced by the students to the application of media power point. The population in this study were students Level 1 Japanese Language Education Universitas Riau as many as 30 people. Descriptive qualitative method used in this study so that in this study only explain, describe and explain the data obtained.From the analysis of the data can be found: 1) based on the results of the questionnaire, 83.3% of respondents answered that the students can be helped with the implementation of media power point in the course bunpou 1 and 96.7% of students can be motivated to learn bunpou 1 in the presence of media power point,2) a student can gain a positive thing when applying media power point on the course bunpou 1 form of increased student interest in following the lectures, the students add to the understanding of the presented material, power point display media were nice and interesting, and3) the constraints faced by students when the application is media power point presentation of Sound (Sound) contained on media power point is less clear.This research can be used as a teaching medium that can help and support in the course bunpou 1. Based on the research results that have been obtained,it is expected to further research the application of media power point of time in order to prepare the media better and better presentation of her voice again.Key Words: Bunpou1, student feedback, positive things, constraints, media power point